Sub GHz Transceiver for Indoor Localisation of Smartphones - Optimising Localisation Accuracy and Device Runtimes - Fudickar, Sebastian (2014)
For many innovative smartphone applications, precise localisation within buildings is a must. Various communication technologies support localisation, with received signal- strength (RSS)-based WiFi localisation being typically applied. However, precise indoor localisation via WiFi transceivers (2.4 GHz frequency band) is a problem, due to the critical energy consumption of the receiver, with frequent localisations resulting in short battery runtimes. The use of Sub GHz transceivers (frequency band 868 MHz), is supposed to be a good alternative, due to their lower power consumption. Considering the accuracy of localisa- tion both techniques have to be investigated in order to find out, if Sub GHz benefits also from the lower frequency band carrier. The main hypothesis of this thesis is therefore to prove that it is possible to achieve com- parable localisation accuracies within buildings with both transceiver techniques. Consid- ering the energy consumption a significant lower level with Sub GHz is expected, which will lead to enhanced runtime of the device. This hypothesis was proven via quantitative experimental studies of localisation accu- racy as well as of device runtimes. This was done by transceiver-specific model-based localisation algorithms that calculate a device location. This is based on received signal strength (RSS) of messages, sent by surrounding beacons. They were optimised in order to achieve low error-distances, floor-error and localisation-error rates. In order to conduct this study under realistic conditions the Efficient Mobile Unit (EMU), a mobile hand-held device, was developed. It contains WiFi and Sub GHz transceivers. EMU is mainly used for device-runtime tests and records RSS samples. RSS samples are input to â€œsimLocâ€, a simulator for evaluation and optimisation. Promising results have been achieved: With the evaluation environment, it was shown, that the optimised ITU-R (recommen- dation) indoor path-loss function with wall-attenuation represents the signal distribution very well. This path-loss function was the most accurate among eight evaluated ones: Compared to the log-distance path-loss function, its localisation-error distances were significantly lower. Not considering the wall attenuation, the accuracy of the indoor path-loss function appeared to be reduced for both transceivers. Additionally, transceiver-specific localisation algorithms were optimised especially for a multi-floor office building. Optimised algorithms for Sub GHz were generally more accurate than the ones for WiFi. Localisation and floor errors could be neglected as they did not harm the overall functionality. Localisation-accuracy was verified in a comparable building also. Specific algorithms were optimised, and showed that Sub GHz transceivers are applicable also for similar buildings, with a minor error-distance variation among both versions. Transceivers' influence on device runtimes was evaluated in a next step. Device runtime has been significantly enhanced (by 35%) by Sub-GHz based localisation. Thus, concerning frequent indoor localisation, advantage of Sub GHz over WiFi in this context has been proven.